Use of Chemical Stimulants in Tapping Resin from Pinus roxburghii - Rajkhowa, S.; Khan, M. A. Waheed (Indian Forester, 1962)
Tapping resin from Pinus roxburghii using a 25cm. (10") wide bark freshened blaze, sprayed with sulphuric acid, yielded about the same as could be expected from two standard Indian blazes put on the same tree. Using standard Indian 10 cm. (4") wide blazes, it was found that spraying sulphuric acid did not result in any increased yield. Spraying a 25% solution of hydrochloric acid on wood chipped blaze along with a 7 day freshening period increased the resin flow by about 18%, but the application of the acid did not permit of using a bark chipped blaze, or of a longer cycle, to yield resin at least equal to the standard tapping.